2018
DOI: 10.5435/jaaos-d-16-00600
|View full text |Cite
|
Sign up to set email alerts
|

Angiography and Embolization in the Management of Bleeding Pelvic Fractures

Abstract: The use, timing, and priority of angioembolization in the management of bleeding pelvic fractures remain ambiguous. The most common vessels for angioembolization are, in decreasing order, the internal iliac artery and its branches, the superior gluteal artery, the obturator artery, and the internal pudendal artery. Technical success rates for this treatment option range from 74% to 100%. The fracture patterns most commonly requiring angioembolization are the Young and Burgess lateral compression and anterior-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 40 publications
2
83
0
3
Order By: Relevance
“…However, pelvic arterial bleeding accounts for up to 15% of bleeding associated with pelvic fractures; this type of bleeding is more threatening than venous bleeding [2, 9, 10]. The most often identified sources of arterial bleeding are the internal iliac artery (IIA) and its branches; patients with pelvic arterial bleeding usually present with systolic blood pressure (SBP) less than 90 mmHg, need more than 2000 mL of fluid resuscitation, and receive more than 4 units of blood transfusion within 24 h [2, 1113]. Transcatheter arterial embolization (TAE) is an effective way to aggressively manage arterial bleeding and has a success rate higher than 85% [5, 10, 1421].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pelvic arterial bleeding accounts for up to 15% of bleeding associated with pelvic fractures; this type of bleeding is more threatening than venous bleeding [2, 9, 10]. The most often identified sources of arterial bleeding are the internal iliac artery (IIA) and its branches; patients with pelvic arterial bleeding usually present with systolic blood pressure (SBP) less than 90 mmHg, need more than 2000 mL of fluid resuscitation, and receive more than 4 units of blood transfusion within 24 h [2, 1113]. Transcatheter arterial embolization (TAE) is an effective way to aggressively manage arterial bleeding and has a success rate higher than 85% [5, 10, 1421].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although the success rate of TAE is high, the mortality rates reported in patients receiving TAE range from 16% to 50% among previous studies [11, 22]. Deaths usually result from associated injuries and delayed TAE [7, 19, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Selection of the optimal treatment of major hemorrhage in patients with pelvic fracture remains a challenge for trauma surgeons (1-7). Uncontrollable major hemorrhage is a major cause of mortality in patients with pelvic fractures (8)(9)(10)(11). Relatively aggressive measures are imperative to manage this serious pathophysiological status; blood transfusion is an effective protocol for the improvement of the hypovolemic status and the use of other supportive care measures, including external fixations, angiography and embolization, as well as pre-peritoneal pelvic packing, may also be effective (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrollable major hemorrhage is a major cause of mortality in patients with pelvic fractures (8)(9)(10)(11). Relatively aggressive measures are imperative to manage this serious pathophysiological status; blood transfusion is an effective protocol for the improvement of the hypovolemic status and the use of other supportive care measures, including external fixations, angiography and embolization, as well as pre-peritoneal pelvic packing, may also be effective (8)(9)(10)(11). Previous studies have revealed that high-energy pelvic fracture is associated with a relatively higher blood transfusion frequency (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Absorbable gelfoam particles, compared with permanent materials such as polyvinyl alcohol particles and trisacryl gelatin microspheres, are preferred because they are temporary embolic materials and without many complications. The complications of embolization for pelvic arteries include infection, necrosis of muscle or penis, nerve injury, bladder or ureteral infarction, bleeding or hemorrhage, bowel infarction, thigh or buttock claudication, and impotence (Vaidya et al, 2018). In this case, gelatin sponge and natural silk segments were used in order to preserve the normal erectile function of the patient.…”
Section: Discussionmentioning
confidence: 99%